1988
DOI: 10.1007/bf00125718
|View full text |Cite
|
Sign up to set email alerts
|

The political economy of development: A cross-national causality test of development-democracy-growth hypothesis

Abstract: BackgroundThe development-democracy-growth hypothesis has received much attention from social scientists. The literature concerned with the level of economic development and prevalence of democratic institutions specifies a causal flow from the former to the latter. Whereas, the literature dealing with the relationship between the rate of economic growth and democratic character of political institutions assumes a causal flow from the latter to the former. The hypothesized development-democracy-growth relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
9

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(29 citation statements)
references
References 13 publications
0
20
0
9
Order By: Relevance
“…A democratic political system creates conditions conducive to growth because it allows the most active and talented citizens to participate fully in business. Other studies have also found a significant positive association between democracy and economic growth, especially in the direction from democracy to growth (see for example Nelson and Singh, 1998;Pourgerami, 1988;Fedderke and Klitgaard, 1998;de Haan et al 2006). In a contribution by Nelson and Singh (1998) it is emphasized, however, that political freedom and democracy in developing countries could undermine the effectiveness of government policy with discipline, law and order.…”
Section: Literature Overviewmentioning
confidence: 87%
“…A democratic political system creates conditions conducive to growth because it allows the most active and talented citizens to participate fully in business. Other studies have also found a significant positive association between democracy and economic growth, especially in the direction from democracy to growth (see for example Nelson and Singh, 1998;Pourgerami, 1988;Fedderke and Klitgaard, 1998;de Haan et al 2006). In a contribution by Nelson and Singh (1998) it is emphasized, however, that political freedom and democracy in developing countries could undermine the effectiveness of government policy with discipline, law and order.…”
Section: Literature Overviewmentioning
confidence: 87%
“…Kormendi and Meguire (1985) studied 47 countries during 1950-1977 and found that democratic countries grew faster. Pourgerami (1988) studied 92 countries during [1965][1966][1967][1968][1969][1970][1971][1972][1973][1974][1975][1976][1977][1978][1979][1980][1981][1982][1983][1984] and found that democratic countries grew faster. Scully (1988; studied 115 countries during and found that democratic countries grew faster.…”
Section: Empirical Relationship Between Political Regime and Developmmentioning
confidence: 99%
“…Er is een aantal studies dat een (iets) afwijkende onderzoekstechniek kiest. Zo baseert Pourgerami (1988) In het onderzoek naar sociaal-economische instituties en ontwikkeling worden de instituties doorgaans als exogeen opgevat. De schaarse studies die sociaaleconomische instituties endogeniseren, rapporteren interessante bevindingen.…”
Section: Onderzoeksmethodenunclassified
“…De schaarse studies die sociaaleconomische instituties endogeniseren, rapporteren interessante bevindingen. Zo stelt Pourgerami (1988) dat marktregulering weliswaar een positief effect heeft op economische groei, maar dat marktregulering deels weer positief wordt beïnvloed door het ontwikkelingsniveau, democratie en cultuur. Clague et al (1997a) constateren dat duurzame democratieën een betere bescherming bieden voor eigendomsrechten dan niet-duurzame politieke regimes en dat duurzame autocratieën eigendomsrechten beter respecteren dan niet-duurzame autocratieën.…”
Section: Onderzoeksmethodenunclassified